Perceived Barriers to Uptake of Cervical Cancer Screening Among Women of Childbearing Age in a Gynaecological Clinic (2019)
Introduction: Cervical cancer is an important reproductive health problem Tor women in the developing countries where it constitutes 13% of all female malignancies. It is the second most common cancer in women worldwide and 83 percent of the world’s 500,000 new cases and 85 percent of the 288,000 cervical cancer deaths occur in developing countries. Evidences show that women attending various health facilities were not routinely screened for cervical cancer. Gynaecological clinics present an important access to target group for cervical cancer screening. This study assessed the barriers to uptake of cervical cancer screening services among women attending a gynaecological clinic of a tertiary health i a tertiary health facility in South West region of Nigeria, the most populous black country of the world. Methodology Adopting a descriptive cross-sectional approach and Health Belief Model (HBM), women aged 15 49 years attending gynaecological clinic at the health institution were interviewed. The respondents were selected using systematic random sampling technique and interviewed using a specially designed structured questionnaire. Barrier to uptake of cervical cancer screening services was defined as significant when the number of the respondents in' the “agree” and “strongly agree” domains to the selected reasons for not screening for cervical cancer are at least 50%. Results Of the 100 respondents interviewed, 85 responses were found suitable for analysis. The mean age of the respondents was 33.3 (SD±8.6) years. Although a large proportion of the respondents (77.1%) were aware of cervical cancer, 95.2% with at least secondary education and 51.9% earning at least N50,000/month, only 23 (27.1%) had undergone the screening for cervical cancer. Age > 44 years and earning > N100,000/month were positively and significantly associated with uptake of cervical cancer screening. The significant reasons for not screening for cervical cancer by the respondents were Lack of information/counselling (77.4%), Lack of convenient clinic time (62.9%), Fear of having a positive result (61.3%), Lack of support from partners and significant others is a barrier (56.5%) and Attitude of health workers discourage women from assessing cervical cancer screening (51.6%) Conclusion It can be concluded from this this study that there is need for need for regular information on cervical screening at every opportunity for the populations that will benefit from this preventive service like women of reproductive age group attending our obstetric services. There is an urgent need for provision of more screening opportunities especially the type that will have population coverage and to leverage on other programmes like family planning services, post-natal clinic services and HIV/AIDS programmes. Screening services should be available in all secondary facilities and primary health care centres. Reminder/Recall services should be in place to ensure compliance with appointments in order to increase utilization